The Influence of Learning Styles on Student Achievement in First Year Students of Sebelas Maret University Faculty of Medicine - Abdillah, Ramadhan; Pamungkasari, Eti Poncorini; Damayanti, Kusmadewi Eka (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
ABSTRACT Background: Knowledge of learning styles is known to be useful for both teachers and students for allegedly influencing student achievement. This study aimed to determine the influence of learning styles on student achievement in first year student. Methods: This research was a comparative analytic research with cross sectional approach to the first year students of Medical Education Sebelas Maret University. There were 186 students as research subjects. Learning styles were measured using VARK questionnaire and student achievement obtained from 2nd semester GPA. Data were analyzed using Kruskal Wallis test and Mann-Whitney and continued with the spearman rank correlation test. Result: Kruskal Wallis test results showed no significant difference among the five groups of learning styles with a value of p = 0.483 (p > 0.05). Mann-Whitney test results also showed no significant differences in individual learning styles (p > 0.05). Spearman rank correlation test results showed no significant influence between learning styles and student achievement (rs < 0.20). Conclusion: There is no significant influence of learning styles on student achievement in first year students. Keyword: learning style, student achievement, VARKÂ